The Integration of Monotheism Values and Ethical Leadership in the Age of AI at Elementary School (Buana Pendidikan: Jurnal Fakultas Keguruan dan Ilmu Pendidikan Unipa Surabaya, 2026)
The development of artificial intelligence (AI) gave a new challenge for Islamic Education, AI has open a new path for efficiency, self-learning and educational management. Without strong spiritual foundation, it would not utilized properly into desired path, likely reshaping a noble morals and benefitting for humanity. This research use qualitative approach through study-case method at SD IT Cita Mulia, through in-dept interview, field observation and analysis on digital technology that applied at the school. The result show that headmaster as central figure combining monotheism values through schools policy. The school successfully build an ethical culture on technogy usage, uphold transparency, responsibility, as well as virtue on digital-based decision. The integration of monotheism value proven to be effective and strengthen islamic-based educational vision.